KEBIJAKAN DESENTRALISASI DAN PROBLEMA KAPASITAS LAYANAN KESEHATAN (Studi Kasus di Kota Bandar Lampung) - Syamsul Ma’arif (Jurnal Administrasi Publik, 2014)
This study is aimed at determining the capacity of health services at the local level after a decade of health decentralization policy implementation. This study uses qualitative research and descriptive type. The results showed that the implementation of the decentralization policy of health for a decade turned out to be characterized by the high gab between the capacity of health services to the complexity of the health problems in the area. For the improvement of the quantity and quality of health services should continue to be done through increased financial capacity, facilities, infrastructure, and medical personnel, who accompanied the expansion of access of the poor to obtain health care services through the provision of health insurance.